Phytosiociological study in Taklong Island, Nueva Valencia, Guimaras, Philippines. - Jimenez, Gladys Mae C.
The IPCC Third Assessment Report confirms that small islands due to their limited size are prone to natural hazards, and external shocks that make them highly vulnerable to climate change, sea-level rise and other extreme events. Small islands have high distribution of species at community and ecosystem level; exposed to several factors, they have considerably diverse and complex flora. A phytosociological study was done in Taklong Island National Marine Reserve in Nueva Valencia, Guimaras to assess the species composition and community structure of vascular plants in the islands. In addition, the study specifically focused on the description, identification and classification of the flora present in the area as well as the description of the overall community structure including its species composition, stand height, stand basal area, basal cover, plant density, important value, species richness, and species diversity. There is a need to study the flora of small islands since they are greatly threatened by the increasing impacts of natural hazards and anthropogenic processes. Results presented that the common life forms observed were mainly trees shrubs and vines. The total sampled area for the six random plots in Taklong Island measured 600 m2 with a total basal cover of 27973.33 m2ha-1. The island?s species diversity was at 0.77 calculated using Shannon?s index of diversity whereas the species evenness of species was found was 0.99. The low level of species diversity implies that the island is not that diverse but this could be due to limited sampling only and not necessarily the true state of its diversity. Despite the low diversity value of the island, evenness of the species was found to be high which implies upright distribution of species in the area. Overall, there were 46 species observed in the sampled sites of the island but only 16 species were recorded in the six plots covered. These 16 species belong to 11 families. The most important species among the plots were Streblus ilicifolius with an IV of 67.58% belonging to the family Moraceae. The species with the highest stand basal area was Carmona retusa with 20.18 m2 ha-1. Wrightia pubescens was also present in all sampled plots. Occurrence of invasive species such as Lantana camara and Leucena leucocephala was also observed in the site. Species having high importance values aid in maintaining the ecological balance of the community and it is recommended to protect these species as well as the others to conserve the biodiversity.